Dinamika Ekonomi Perdesaan: Proses Adopsi Masyarakat Lokal Terhadap Komoditas Sawit - Sukapti Wartiharjono (DIMENSI - Journal of Sociology, 2016)
This paper aims at describing the introduction and adoption process of society to the commodity plants of palm plantation supporting economic dynamics of rural society. Field study was conducted with phenomenology method, deep- interview and participated observation to arrange data. Phenomenology approach conducted in this research resulted in finding that palm plantation was introduced and developed by the government through power approach to the society in rural area. Horizontal and vertical conflict in accompanying the entry of the palm plantation did not mean of refusing of farmers to the commodity of palm plantation, but it was an effort to access for better positions. Furthermore, small farmers accessed quickly and with eagerness to the arena of capitalist production mode and left the traditional plantation farm modes.